Occurrence of viruses and Xiphinema spp. in vineyards of the greek islands of Paros and Lemnos - Avgelis, Apostolos D.; Tzortzakakis, Emmanuel A. (Phytopathologia Mediterranea, 2001)
A survey was carried out during 1997–2000 in order to determine the incidence of grapevine viruses and their associated nematode-vectors in Paros and Lemnos, the two main islands of the Aegean sea producing V.Q.P.R.D. wines. Nine viruses, Grapevine fanleaf nepovirus (GFLV), Grapevine leafroll associated closterovirus (GLRaV) 1, 2, 3, 6 and 7, Grapevine vitivirus (GV) A and B, Grapevine fleck virus (GFkV) and three species of Xiphinema, X. index, X. italiae and X. pachtaicum, were recorded. While the three nematode species occurred in both islands, the virological problems of each island were different. In Paros, GFLV and its vector X. index were widespread in selfrooted vineyards, while GVA also occurred in asymptomatic vines. In Lemnos, where vineyards use American rootstocks, the Closteroviruses and GVA were the major problem, explaining the high incidence of leafroll and stem grooving.